Weevils tame unruly hyacinth - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
A new control methodology that uses weevils has resulted in a near 80% reduction of the notorious water hyacinth, Eichornia crassipes, in Uganda. As weevil damage reduces leaf area and root length, the affected plants cannot grow or produce new...